GAMBARAN POLA PERESEPAN OBAT DIARE PADA PASIEN ANAK DI RSUD H. ABDUL MANAP JAMBI PERIODE JANUARI – MARET TAHUN 2022 - Supriadi; Dahlan, Ahmad (PHARMANAJA : PHARMACEUTICAL JOURNAL OF UNAJA, 2023)
Diarrhea is the second leading cause of death in children under five years old. Globally, there are 1.7 billion cases of diarrhea every year and around 525,000 children die each year. Objective of this study is to describe the pattern of diarrhea drug prescribing in children based on the type of drug and other therapeutic drug classes. The type of research used is descriptive quantitative. The population and sample in this study were all prescription sheets of pediatric patients with a diagnosis of diarrhea, namely there were 26 patient prescriptions and the method used in this study was saturated sampling. The results of the study of 26 pediatric patients showed that the most commonly prescribed diarrhea drugs were zinc and L-Bio (36.5%). Based on other therapeutic drug groups, the highest percentage of drug use is Antiemitics (100.0%). In Conclusion, Diarrhea drug prescribing based on the type of diarrhea medication that was most often prescribed was Zinc and L-Bio, each amounting to (36.5%). Other Therapeutic Drugs that are widely used or combined with children's diarrhea